EFFECTIVE VOCABULARY DEVELOPMENT STRATEGIES FOR YOUNG LEARNERS IN ENGLISH LANGUAGE EDUCATION - Anorboyeva Kamola Mamarajab qizi (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2026)
Abstract. Vocabulary knowledge plays a crucial role in developing young learners’ English language proficiency. Effective vocabulary instruction helps children improve their listening, speaking, reading, and writing skills. This article discusses three essential strategies for vocabulary development among young learners: contextual learning, visual and multisensory techniques, and repeated exposure through meaningful activities. These approaches contribute to long-term vocabulary retention and support overall language acquisition.